Dynamic mentoring for civil engineers - Steels, H. Macdonald (Thomas Telford, 2001)
In order to maximise the skills, abilities and commitment of its workforce, a company must make training a part of their business development. To develop employees' potential, as quickly as possible, requires mentors who need to be carefully chosen and better trained to undertake this vital role.